Socio-urban aspects of the pandemic crisis in Serbia - Božilović, Jelena; Petkovic, Jelena (Sociološki pregled, 2020)
The paper deals with the discussion of cities from a socio-ecological perspective, from the standpoint of health and quality of life from the time of the first industrialisation to the current social crisis. Rethinking the connection between health and life in the city in modern social theory has resulted in new constructive concepts of the city, and some ideas of such concepts in the current situation may be guidelines for the development of cities of the future. The second segment of the paper is based on the analysis of selected results of the broader empirical research conducted in 2020 by anonymous online survey and applying comparative-analytical and statistical methods. The respondents’ views on the quality of life in the city and countryside at the time of the pandemic generally show that, despite the fact that the respondents evaluate the countryside more positively than the city, their attitude is such that minority of them agree with the fact that the experience with the pandemic will direct people to life outside cities in the future.
Keywords: city; pandemic; healthy city; countryside; urban planning